Differences in the Effects of Square Stepping Exercise and Gaze Stability Exercise on Balance in Older Adults at the Elok Edy Health Center - Gia Oktavia Desisca; Lailatuz Zaidah; M. Ali Jafar (Journal Research of Social Science, Economics, and Management, 2026)
Elderly individuals often face balance disorders, with the World Health Organization (WHO) reporting that approximately 28-35% of the elderly worldwide are at increased risk of falls. According to the Central Statistics Agency (BPS) 2022, 10.48% of the total population and 31-48% of the elderly population experience balance disorders, which affect 6,969 elderly individuals (BPS 2021) in Sleman, Indonesia. These issues can lead to injuries and reduce quality of life. Square Stepping Exercise (SSE) and Gaze Stability Exercise (GSE) have been shown to be effective in improving balance in the elderly. These are non-pharmacological interventions that can help address balance problems through physical activity. However, the comparison of their effects has not been extensively researched. This study aims to determine whether both types of exercises can improve balance in the elderly and to assess the effectiveness of each exercise in enhancing balance among the elderly at the Elok Edy Elderly Posyandu, Rajek Wetan, Melati, Sleman, Yogyakarta. This research used a quantitative approach with a quasi-experimental design, utilizing a pre-test and post-test with two groups. The total number of respondents was 36 elderly individuals who experienced mild to moderate balance disturbances, divided into two groups: the SSE intervention group (n=18) and the GSE intervention group (n=18).  This study shows that both types of exercises, Square Stepping Exercise (SSE) and Gaze Stability Exercise (GSE), have a positive impact on improving balance in the elderly. The p-value (Sig) obtained for both tests is p = 0.000, indicating statistical significance.